2012
DOI: 10.1001/archinternmed.2012.1804
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pulmonary Embolism in the Emergency Department and Consistency With a National Quality Measure

Abstract: Background The National Quality Forum (NQF) has endorsed a performance measure designed to increase imaging efficiency for the evaluation of pulmonary embolism (PE) in the emergency department (ED). To our knowledge, no published data have examined the effect of patient-level predictors on performance. Methods To quantify the prevalence of avoidable imaging in ED patients with suspected PE, we performed a prospective, multicenter observational study of ED patients evaluated for PE from 2004 through 2007 at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 21 publications
6
68
0
Order By: Relevance
“…Among them, only 43% received further D-dimer assays as per the guidelines, while the rest underwent CTPAs without D-dimers ordered. This has been reported in previous studies documenting underutilization of the D-dimer assay in the low-risk group in emergency departments across the US [13,18]. …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Among them, only 43% received further D-dimer assays as per the guidelines, while the rest underwent CTPAs without D-dimers ordered. This has been reported in previous studies documenting underutilization of the D-dimer assay in the low-risk group in emergency departments across the US [13,18]. …”
Section: Discussionsupporting
confidence: 63%
“…In other words, these patients were exposed to unnecessary risks of radiation and contrast exposure. Other studies have reported numbers of avoidable imaging ranging from as low as 33% up to 71%; the difference in the reported numbers is mainly due to differences in physicians’ practices and adherence to guidelines [14,17,18]. A very plausible explanation for these patients receiving inappropriately ordered CTPAs is that physicians did not pursue further D-dimer testing in 98% of the cases to further classify the patients as low- or high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 A recent multicentre study found that emergency physicians overuse CT in the investigation of PE and image more than half of low-risk patients. 21 One-third of ED patients evaluated for PE will later be re-evaluated with a second CT scan, despite limited diagnostic yield. 22 In our study, one in six patients scanned had a positive CT scan for PE, a rate comparable to that of a published trial of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the majority of patients will ultimately have neither diagnosis, physicians order numerous laboratory tests and advanced imaging for patients with complaints referable to the chest. 2,3 Those designing clinical protocols for evaluation of possible acute coronary syndrome and PE remain keenly interested in developing guidelines that maximize patient safety by achieving a high degree of diagnostic certainty while minimizing length of stay and cost. 4,5 Toward this goal, it is important to recognize that salient patient phenotypes, such as patient body mass index (BMI), may predict more complex and costly care to achieve the same degree of diagnostic certainty as for a normal weight individual.…”
mentioning
confidence: 99%